2009
DOI: 10.1177/230949900901700119
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Lumbar Apophyseal Ring Fractures in Adolescents: A Report of Four Cases

Abstract: Posterior lumbar apophyseal ring fractures are rare in adolescents. We report 4 such cases in Chinese adolescents. Two of the patients had a slipped capital femoral epiphysis; 3 of them were overweight/obese. All presented with low back pain and radicular pain. Apophyseal fractures of the upper lumbar spine usually involve the lower end plate, whereas those of the lumbar sacral spine usually involve the upper end plate. The radiological features and pathophysiology are discussed. Two of the patients were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…Surgery is done via a posterior approach to remove the offending fragments with or without an interlaminal laminectomy. 13,35 Typically these are not unstable injuries, and thus fusion is not necessary and outcomes are usually favorable.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is done via a posterior approach to remove the offending fragments with or without an interlaminal laminectomy. 13,35 Typically these are not unstable injuries, and thus fusion is not necessary and outcomes are usually favorable.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…33 Yen et al reported 4 adolescent cases and noted a strong association of adolescent apophyseal ring fractures with a slipped capital femoral epiphysis and overweight/obesity. 35 The patient in Case 4 was a 13-year-old girl who fell on her tailbone while playing volleyball and developed acute onset of back pain with radicular pain down her left posterior extremity to the dorsum of her left foot. A CT scan was done, which demonstrated a posterior detached fragment at the superior S-1 endplate and a defect in the bone adjoining the fracture site ( Fig.…”
Section: Apophyseal Ring Fracturesmentioning
confidence: 99%
“…49 Surgical intervention depends on clinical symptoms. [48][49][50] Scheuermann Kyphosis (Juvenile Kyphosis) Scheuermann kyphosis is an osteochondrosis presenting as an abnormality of the vertebral epiphyseal growth plates. 18 This condition presents as a form of adolescent thoracic or thoracolumbar kyphosis characterized by anterior wedging of 3 or more contiguous vertebrae of 5°or greater resulting in a thoracic kyphosis greater than 35°, with the apex more commonly seen between T7 and T9.…”
Section: Disk Degeneration and Herniationmentioning
confidence: 99%
“…Thoracolumbar SCIWORA has an occurrence up to 50% in such patients, matched to less than 1% in adults (45,46).…”
Section: Injury Based Of Child Agementioning
confidence: 99%
“…Children above 4 years old have expanded child care seats; however, do not have established iliac crests to attend as anchor points for lap belts (46,47).…”
Section: Less Than 12 Years Oldmentioning
confidence: 99%